S.O.B (Save Our Budget) - A Simulation-Based Method for Prediction of Acquisition Costs of Constituents of aSystem-of-Systems - Graciano Neto, Valdemar Vicente; Horita, Flávio Eduardo Aoki; Santos, Rodrigo; Viana, Davi; Kassab, Mohamad; Manzano, Wallace; Nakagawa, Elisa Yumi (Histórico da iSys - Brazilian Journal of Information Systems (SERVIDOR ANTIGO - UNIRIO), 2019)
Software economics, acquisition, and pricing are important concerns for Systems-of-Systems (SoS). SoS are alliances of independent software-intensive systems combined to offer holistic functionalities as a result of the constituents interoperability. SoS engineering involves separately acquiring constituents and combining them to form the SoS. Despite the existence of cost prediction techniques, predicting SoS acquisition costs at design-time should also include the analysis of different suppliers of constituents, their respective prices and quality. However, known methods cover only two out of these three parameters.  The main contribution of this article is to present the S.O.B. (Save Our Budget) method, a novel simulation-based method to predict, at design-time, the acquisition cost of constituents, while still considering quality attributes and different suppliers. Results of a case study in the Smart Building domain revealed that S.O.B. method supports a precise prediction of acquisition cost of constituents to build a SoS for that domain. Furthermore, it also contributes to estimate the cost based on a pre-established quality attribute (functional suitability), as well as to support the selection of coalition that exhibits better results through the analysis of cost-benefit ratio.